BIMG-16. TRACKING TTFIELDS-INDUCED ALTERATIONS IN GLIOBLASTOMA METABOLISM WITH [18F]DASA-23, A NON-INVASIVE PROBE OF PYRUVATE KINASE M2 (PKM2). (25th March 2021) - Patel, Chirag; Beinat, Corinne; Xie, Yuanyang; Chang, Edwin; Gambhir, Sanjiv
Abstract: Despite the anti-proliferative and survival benefits from tumor treating fields (TTFields) in human glioblastoma (hGBM), little is known about the effects of this form of alternating electric fields therapy on the aberrant glycolysis of hGBM. [18F]FDG is the most common radiotracer in cancer metabolic imaging, but its utility in hGBM is impaired due to high glucose uptake in normal brain tissue. With TTFields, radiochemistry, Western blot, and immunofluorescence microscopy, we identified pyruvate kinase M2 (PKM2) as a biomarker of hGBM response to therapeutic TTFields. We used [18F]DASA-23, a novel radiotracer that measures PKM2 expression and which has been shown to be safe in humans, to detect a shift away from hGBM aberrant glycolysis in response to TTFields. Compared to unexposed hGBM, [18F]DASA-23 uptake was reduced in hGBM exposed to TTFields (53%, P< 0.05) or temozolomide chemotherapy (33%, P > 0.05) for 3 d. A 6-d TTFields exposure resulted in a 31% reduction (P = 0.043) in 60-min uptake of [18F]DASA-23. [18F]DASA-23 was retained after a 10 but not 30-min wash-out period. Compared to [18F]FDG, [18F]DASA-23 demonstrated a 4- to 9-fold greater uptake, implying an improved tumor-to-background ratio. Furthermore, compared to no-TTFields exposure, a 6-d TTFields exposure caused a 35% reduction in [18F]DASA-23 30-min uptake compared to only an 8% reduction in [18F]FDG 30-min uptake. Quantitative Western blot analysis and qualitative immunofluorescence for PKM2 confirmed the TTFields-induced reduction in PKM2 expression. This is the first study to demonstrate that TTFields impairs hGBM aberrant glycolytic metabolism through reduced PKM2 expression, which can be non-invasively detected by the [18F]DASA-23 radiotracer.